Statistical Analysis of Water Quality Parameters in Downstream of Nan River, Thailand - Khanitchaidecha, Wilawan; Pitakwinai, Pichapong; Ratananikom, Khakhanang; Nakaruk, Auppatham (Naresuan University Engineering Journal, 2019)
The water quality analysis of the downstream of Nan river during 2012 to 2016 was carried out in this study. The secondary water quality data of 15 parameters in four station sites of NA07, NA05, NA03 and NA02 was provided by Pollution Control Department, Ministry of Natural Resource and Environment. The water quality index (WQI), which was calculated from 5 main parameters of dissolved oxygen, BOD, total coliform bacteria, fecal coliform bacteria and ammonia, was used to evaluate and monitor the water quality and together with statistical programmes (i.e., ANOVA, t-test, SPSS). The results presented that the average WQI was significantly decreasing by station sites; the value was around 70 at Station NA07 which is close to the midstream of Nan river, the value was 67 at Station NA05 which are the latter area, and the values were 62 and 61 at Stations NA03 and NA02 which are the furthest. Although the average WQI of all stations was categorized in moderate quality, the minimal WQIs of Stations NA05, NA03 and NA02 were categorized in poor quality. Nan river is potential area for water pollution. The significant parameters affecting the poor water quality were BOD, total coliform bacteria, fecal coliform bacteria. According to HCA analysis, the BOD was classified in the same component of turbidity, total solids and suspended solids which are easily measured. In the meanwhile, both bacteria were classified in the same component of pH. Therefore, the latter parameters can be used as primary parameters for pollution prevention in downstream of Nan river.